Poverty and Health: Working with Families - Blackburn, Clare (Open University Press, 1991)
This book is concerned with the impact of poverty on health, focusing on families with young children in the United Kingdom. It draws together information from a wide range of disciplines to provide workers in the health and welfare fields with a better understanding of the complex interconnections between living conditions, lifestyles, and health problems. Chapters 1 and 2 introduce the context of the exploration, and the next four chapters examine how poverty affects the health of those who experience it. Chapters explore the specific issues of nutrition and food, housing, mental health, and caring for children's health. Chapter 7 summarizes the main themes and identifies the major issues with implications for public policy. High unemployment, low pay, and cuts in public expenditures have worked to make it more difficult to maintain a decent standard of living, particularly for the urban and minority poor. The pressure for health and welfare workers to understand the links between poverty and health is greater than ever. References follow each chapter. (Contains eight figures and nine tables.) (SLD)